Multi-objective design optimization of bulk carriers - Hadj Mohamed, Baghdad; Belkadi, M.; Aounallah, M.; Adjlout, L. (Journal of Naval Architecture and Marine Engineering, 2023)
This paper deals with the numerical optimization of bulk carrier design. The main objective is to minimize the construction cost, the transportation cost and to maximize the annual transported cargo. Four multi-objective optimization methods are used: the weighted aggregation method based on multi-attribute decision making (MADM), the control function, the Non-dominated Sorting Genetic Algorithm (NSGA-II) and the hybrid method. The obtained results show that the MADM, NSGA-II and hybrid methods give more or less similar results for the three objective functions compared to the control function method. They also showed that although the weighted aggregation method MADM has certain advantage related to construction cost and voyage cost compared to both NSGA-II and hybrid methods, it remains deficient with regard to the transportation cost and the annual transported cargo.